The Impact of The Participation and The Satisfaction of Users in The Development of The Information System with The Complexity of System and The Strucure of Organization as Moderatinbg Variables - Dian Indri Purnamasari; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
This study extents the research conducted by McKeen et. al (1994) by re-examining the relationship between the participation of users and the their satisfaction in the development of information system. The complexity of system will be used as a moderating variable in that research. This research will also add organization structure as a moderating variable that has not been used in the relationship between the participation of users and their satisfaction in the development of the information system.Given the response rate of 19%, the analysis indicated that the complexity of system statistically influenced the relationship between the participation of users and the satisfaction of them. The stronger was the influence, the higher the complexity of the system was. The organization structure statistically did not influence the relationship between the participation of users and the satisfaction of them. The interaction between the participation of users and the organization structure was not significant and hence it could not be included that the influence was increasingly high when the organization used the decentralized structure.